Can migration be a conduit for transformative youth employment? - Mueller, Valerie; Lee, Hak Lim (International Food Policy Research Institute, 2019)
Chapter 2 uses new household survey data to investigate youth migration patterns in four African countries, paying particular attention to the effect of land scarcity on young people’s decision to migrate to urban centres. Despite urbanization, rural job creation is a major policy goal for many African governments. However, it is unclear whether national polices adequately reflect and address the constraints facing young job seekers in agriculture and rural areas.